1996
DOI: 10.1136/bmj.313.7065.1119
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for lower respiratory complications of rhinovirus infections in elderly people living in the community: prospective cohort study

Abstract: Objective-To assess the role of rhinoviruses in elderly people living in the community.Design-Prospective community based surveillance of elderly people, without intervention. Subjects were telephoned weekly to identify symptomatic upper respiratory tract infections. Symptoms and impact of illnesses were monitored, and specimens were collected for diagnostic serology and human rhinovirus polymerase chain reaction.Setting-Leicestershire, England. There were almost six times as many symptomatic rhinovirus infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
91
2
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 34 publications
(39 reference statements)
7
91
2
3
Order By: Relevance
“…The definition of lower respiratory tract involvement in the latter studies was less stringent than that defining exacerbation in the present report. Therefore, it is suggested, in agreement with GREENBERG et al [13], that COPD patients as a group are not more susceptible to respiratory viral infections, and, in agreement with NICHOLSON and coworkers [16,17], that patients with COPD do not appear more likely to develop lower respiratory tract symptoms during such events than other elderly subjects. However, the current authors have shown that cold frequency in COPD is variable, and this masks an important effect in frequent exacerbators who do indeed have an increased frequency of colds.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The definition of lower respiratory tract involvement in the latter studies was less stringent than that defining exacerbation in the present report. Therefore, it is suggested, in agreement with GREENBERG et al [13], that COPD patients as a group are not more susceptible to respiratory viral infections, and, in agreement with NICHOLSON and coworkers [16,17], that patients with COPD do not appear more likely to develop lower respiratory tract symptoms during such events than other elderly subjects. However, the current authors have shown that cold frequency in COPD is variable, and this masks an important effect in frequent exacerbators who do indeed have an increased frequency of colds.…”
Section: Discussionsupporting
confidence: 75%
“…The incidence and clinical features of upper respiratory tract viral infection in community studies of the elderly have been reported by NICHOLSON and coworkers [16,17]. Here, the annual incidence rate was 1.2?patient -1 ?yr -1 , similar to the current data, and, in 63% of patients with documented rhinoviral infections, there was evidence of lower respiratory tract involvement.…”
Section: Discussionmentioning
confidence: 68%
“…Overwhelming evidence exists that cigarette smoke is also associated with a significant increase in the risk of respiratory infections, and smoking is associated with both increased prevalence and severity of upper respiratory infections (URIs) (2)(3)(4)(5). Exposure to cigarette smoke is a major risk factor for the development of URIs in children (6), and was identified as a risk factor in lower respiratory tract complications of rhinovirus infection in older adults (7). Furthermore, a recent study found that patients hospitalized because of rhinovirusinduced exacerbations of asthma were significantly more likely to be current smokers than nonsmokers (odds ratio, 11.2) (8).…”
mentioning
confidence: 99%
“…Furthermore, the pathogenic role of HRVs in lower respiratory tract infections of infants, elderly and immunocompromised patients has been reported [6][7][8].…”
mentioning
confidence: 99%